EVALUATION OF ANTI-INFLAMMATORY AND ANTIDIABETIC ACTIVITY OF SIMAROUBA GLAUCA BARK EXTRACT: AN IN VITRO STUDY - R, ALEESHA; MISHRA, BHARAT (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The present study was envisaged to identify the effect of anti-inflammatory and antidiabetic activity for methanolic bark extracts of Simarouba glauca. Methods: The present study design was to evaluate the in vitro anti-inflammatory and in vitro antidiabetic activity of S. glauca methanolic bark extract. To examine the antidiabetic activity, the samples were studied for their effect on inhibition of alpha-amylase and glucose transport across the dialysis membrane. In vitro anti-inflammatory activity was evaluated using albumin denaturation assay and membrane stabilization method. Results: Our current results indicate that the various bioactive constituents detected in S. glauca may be responsible for its in vitro antidiabetic and anti-inflammatory effects. The ability of plant extract on anti-inflammatory activity showed that it was effective in inhibiting heat-induced albumin denaturation with an IC50 value of test and standard was found to be 46.42 μg/ml and 24.09 μg/ml. In addition to this, heat-induced hemolysis was also performed. The IC50 values of the test and standard were found to be 43.51 μg/ml and 21.41 μg/ml, respectively. The percentage inhibition of the test sample varied from the concentration range of 75 to 100 μg/ml. The IC50 value of the test and standard was found to be 19.08 μg/ml and 9.08 μg/ml, respectively. Conclusion: The findings of the present study concluded that S. glauca bark has the potential to treat diabetes and a novel natural anti-inflammatory agent as a good source. Thus, S. glauca may be a potential candidate for the development of future antidiabetic and anti-inflammatory compounds. However, still further studies and standardization of the plant research may be required to develop them as medicine.